IMPORTANCE OF INTEGRATION OF INFORMATION TECHNOLOGIES IN NATURAL SCIENCES - Mahliyo Sobirova (Web of Journals Publishing, 2024)
The article talks about the integration of information technologies in natural sciences and its importance.
Keywords: information technologies, natural sciences, integration, communication.